Spatial and Interannual Patterns in High-Frequency Oxygen Dynamics and Hypoxia Metrics in the Eutrophic Patuxent River Estuary - Amir Reza Azarnivand; Walter R. Boynton; Jeremy M. Testa (Estuaries and Coasts, 2026)

Modeling the sensitivity of hypoxic area and benthic macrofaunal biomass to nutrient reduction and warming in Chesapeake Bay - Allison Dreiss; Ryan E. Langendorf; Ryan J. Woodland; Vyacheslav Lyubchich; Jeremy M. Testa (Estuarine, Coastal and Shelf Science, 2026)

Potential impacts of invasive mussels on long-term carbonate chemistry changes in Lake Michigan - Chunqi Shen; Jeremy M. Testa; Yang Song (Journal of Oceanology and Limnology, 2026)

Importance of Estuary–Ocean Exchange on Hypoxia in Mid-Lower Chesapeake Bay - Zhengui Wang; Y. Joseph Zhang; Jian Shen; Jeremy M. Testa; Carl Cerco; Lewis Linker; Richard Tian; Wenfan Wu (Estuaries and Coasts, 2026)
In previous water quality modeling studies in Chesapeake Bay, the severity of summer hypoxia tended to be underestimated in the mid-lower Bay area. The underlying reason has not been well understood. In this study, we test a new hypothesis with respect to the estuary–ocean exchange. This hypothesis was motivated by observed high levels of dissolved organic carbon (DOC) near the Bay mouth that, if transported into the Bay, could potentially draw down the dissolved oxygen (DO) in the mid-lower Bay through the microbial respiration of DOC. Using a high-resolution 3D water quality model that includes both the Bay and a portion of the coastal ocean, we provide evidence that supports this hypothesis and demonstrates the important connection between the Bay and the coastal ocean that entrains DOC into the mid-lower Bay during the summer hypoxic season, which leads to a more realistic representation of DO dynamics there. We also outline remaining research questions about the DOC reactivity and sources in the Chesapeake Bay that warrant further study.

Turbulent erosion of a subducting intrusion in the Western Mediterranean Sea - Giovanni Testa; Mathieu Dever; Mara Freilich; Amala Mahadevan; T. M. Shaun Johnston; Lorenzo Pasculli; Francesco M. Falcieri (Ocean Science, 2025)
Frontal zones within the Western Alboran Gyre (WAG) are characterized by a density gradient resulting from the convergence of Atlantic and Mediterranean waters. Subduction along isopycnals at the WAG periphery can play a crucial role in upper-ocean ventilation and influences its stratification and biogeochemical cycles. In 2019, physical parameters (comprising temperature, salinity, turbulent kinetic energy dissipation rates) and biogeochemical data (oxygen and chlorophyll a) profiles were collected in transects along the northern edge of the WAG. Several intrusions of subducted water with elevated oxygen, chlorophyll a, and spice anomaly were identified towards the center of the anticyclone. These features had elevated kinetic energy dissipation rates on both their upper and lower boundaries. Analysis of the turbulent fluxes involving heat, salt, oxygen, and chlorophyll a demonstrated a net flux of physical and biogeochemical properties from the intrusions to the surrounding ocean. Either the turbulent or diffusive convection mixing contributed to the observed dilution of the intrusion. Other factors (e.g., water column density stability, variability of the photic layer depth, and organic matter degradation) likely played a role in these dynamics. Enhanced comprehension of the persistence and extent of these features might lead to an improved quantitative parameterization of relevant physical and biogeochemical properties involved in subduction within the study zone.

Conference Report: Cerebellar Development and Disease at Single-Cell Resolution - Lena M. Kutscher; Davide Aprile; N. Sumru Bayin; Esther B. E. Becker; Valentina Cerrato; Giacomo Turrini; Marion Coolen; Vincent Cantagrel; Béatrice C. Durand; Myron K. Evans II; Parthiv Haldipur; Kathleen J. Millen; et al. (The Cerebellum, 2025)

Assessing the spatial variability of cage movement and velocity attenuation of an off-bottom oyster farm and its influence on eastern oyster (Crassostrea virginica) growth performance - Brendan Campbell; Cassie Gurbisz; Jeremy M. Testa; Edward Hale; Matthew W. Gray (Aquaculture, 2025)

Climate resilience and profitability thresholds in Chesapeake Bay oyster aquaculture - Matt A. Weber; Lisa A. Wainger; Jeremy M. Testa; George G. Waldbusser; Ming Li (Journal of Environmental Management, 2024)

Controls on Water-Column Respiration Rates in a Coastal Plain Estuary: Insights from Long-Term Time-Series Measurements - David Prichett; Joan M. Bonilla Pagan; Casey L. S. Hodgkins; Jeremy M. Testa (Estuaries and Coasts, 2024)

Controls on Oxygen Variability and Depletion in the Patuxent River Estuary - Allison Dreiss; Amir Reza Azarnivand; Anna Hildebrand; Seyedeh Fardis Pourreza Ahmadi; Syeda Sadia Ali; Veronica Malabanan Lucchese; Qian Zhang; Laura L. Lapham; Ryan J. Woodland; Lora Harris; Jeremy M. Testa (Estuaries and Coasts, 2024)
Oxygen depletion in coastal waters is increasing globally due primarily to eutrophication and warming. Hypoxia responses to nutrient loading and climate change have been extensively studied in large systems like the Chesapeake Bay and the Baltic Sea, while fewer studies have investigated smaller, shallower hypoxic zones. Thus, an improved understanding of the interactions of eutrophication and warming on hypoxia expansion (or reduction) in the wide variety of different estuarine environments is needed. We examined interannual controls on oxygen depletion in the Patuxent River estuary, a eutrophic sub-estuary of Chesapeake Bay where seasonal hypoxia develops annually. We conducted a spatial and temporal analysis of dissolved oxygen (DO) trends, timing, and several metrics of depletion over a long-term record (1985–2021). We found an internally generated hypoxic zone that initiates in the middle estuary, spreading upstream and downstream as the summer progresses, and that hypoxic volume days (HVD) have been increasing (0.11 per year, p = 0.03) over the record despite reduced watershed nitrogen loads and stable phosphorus loads. River flow and temperature have been increasing and are major drivers of increased HVD, with river flow explaining 40% of the interannual variation in HVD (temperature has increased 0.03 and 0.06 °C per year in summer and fall, respectively). Apparent oxygen utilization (AOU) is increasing in bottom waters in the fall, consistent with increasing trends of both water temperature and stratification strength. HVD was negatively related ( r 2 = 0.34, slope = −0.59*HVD) to the biomass of benthic invertebrates in the middle region of the estuary, suggesting that benthic forage for higher trophic levels will be limited by sustained hypoxia. These results indicate that current and future climate variability plays an important role in regulating oxygen depletion in the Patuxent River estuary, which reinforces the need to factor climate change into strategies for the restoration and management of estuaries.

Combination and summary of ATLAS dark matter searches interpreted in a 2HDM with a pseudo-scalar mediator using 139 fb−1 of s = 13 TeV pp collision data - G. Aad; B. Abbott; K. Abeling; N.J. Abicht; S.H. Abidi; A. Aboulhorma; H. Abramowicz; H. Abreu; Y. Abulaiti; A.C. Abusleme Hoffman; B.S. Acharya; C. Adam Bourdarios; et al. (Science Bulletin, 2024)

Association of body mass index with progression from binge-eating behavior into binge-eating disorder among adolescents in the United States: A prospective analysis of pooled data - Abubakr A.A. Al-shoaibi; Jason M. Lavender; Sean J. Kim; Iris Yuefan Shao; Kyle T. Ganson; Alexander Testa; Jinbo He; David V. Glidden; Fiona C. Baker; Jason M. Nagata (Appetite, 2024)

P06-20 OMICs approaches linking effects of endocrine disrupters on developing rat hippocampus with impaired memory function in adult offspring and human stem cell-derived in vitro models - W. Lichtensteiger; C. Bassetti-Gaille; H. Rehrauer; N. Caporale; B. Linillos Pradillo; L. Rancan; H. Idrissi; L. Miguélez-Salas; J. Felix; S.D. Paredes; S. Evangelista; M. de la Fuente; et al. (Toxicology Letters, 2024)

OS04-03 Unravelling the impact of endocrine disruptors on human neurodevelopment through the lens of brain organoids - M. Lessi; N. Caporale; M.T. Rigoli; C. Cheroni; S. Stucchi; G. Matassa; D. Bulgheresi; A. Valenti; G. Testa (Toxicology Letters, 2024)

Physical and Biological Controls on Short-Term Variations in Dissolved Oxygen in Shallow Waters of a Large Temperate Estuary - Jeremy M. Testa; Wei Liu; Walter R. Boynton; Denise Breitburg; Carl Friedrichs; Ming Li; David Parrish; T. Mark Trice; Damian C. Brady (Estuaries and Coasts, 2024)

Clinical presentation, echocardiographic findings, treatment strategies, and prognosis of dogs with myxomatous mitral valve disease presented with pericardial effusion due to suspected left atrial tear: a retrospective case–control study - A.A. Czech; T.M. Glaus; F. Testa; G. Romito; M. Baron Toaldo (Journal of Veterinary Cardiology, 2024)

Interannual variability of air-water CO2 flux in a large eutrophic estuary - Chunqi Shen; Jeremy M. Testa; Ming Li; Baoshan Chen; Wei-Jun Cai (Water Research, 2023)

Life Cycle Assessment of a system for the extraction and transformation of Waste Water Treatment Sludge (WWTS)-derived lipids into biodiesel - B. Notarnicola; G. Tassielli; P.A. Renzulli; R. Di Capua; F. Astuto; S. Riela; A. Nacci; M. Casiello; M.L. Testa; L.F. Liotta; C. Pastore (Science of The Total Environment, 2023)

Large-Scale Spatial and Temporal Patterns and Importance of Sediment–Water Oxygen and Nutrient Fluxes in the Chesapeake Bay Region - W. R. Boynton; M. A. C. Ceballos; C. L. S. Hodgkins; D. Liang; J. M. Testa (Estuaries and Coasts, 2023)

A hydrodynamic model–based approach to assess sampling approaches for dissolved oxygen criteria in the Chesapeake Bay - Dong Liang; Jeremy M. Testa; Lora A. Harris; Walter R. Boynton (Environmental Monitoring and Assessment, 2023)

Simulation of high-frequency dissolved oxygen dynamics in a shallow estuary, the Corsica River, Chesapeake Bay - Richard Tian; Xun Cai; Jeremy M. Testa; Damian C. Brady; Carl F. Cerco; Lewis C. Linker (Frontiers in Marine Science, 2022)
Understanding shallow water biogeochemical dynamics is a challenge in coastal regions, due to the presence of highly variable land-water interface fluxes, tight coupling with sediment processes, tidal dynamics, and diurnal variability in biogeochemical processes. While the deployment of continuous monitoring devices has improved our understanding of high-frequency (12 - 24 hours) variability and spatial heterogeneity in shallow regions, mechanistic modeling of these dynamics has lagged behind conceptual and empirical models. The inherent complexity of shallow water systems is represented in the Corsica River estuary, a small basin within the Chesapeake Bay ecosystem, where abundant monitoring data have been collected from long-term monitoring stations, continuous monitoring sensors, synoptic sensor surveys, and measurements of sediment-water fluxes. A state-of-the-art modeling system, the Semi-implicit Cross-scale Hydroscience Integrated System Model (SCHISM), was applied to the Corsica domain with a high-resolution grid and nutrient loads from the most recent version of the Chesapeake Bay watershed model. The Corsica SCHISM model reproduced observed high-frequency variability in dissolved oxygen, as well as seasonal variability in chlorophyll-a and sediment-water fluxes. Time-series signal analyses using Empirical Model Decomposition and spectral analysis revealed that the diurnal and M2 tide frequencies are the dominant high-frequency modes and physical transport contributes a larger share to dissolved oxygen budgets than biogeochemical processes on an hourly time scale. Heterogeneity and patchiness in dissolved oxygen resulting from phytoplankton distributions and geometry-driven eddies amplify the physical transport effect, and on longer time scales oxygen is controlled more by photosynthesis and respiration. Our simulation demonstrates that interactions among physical and biological dynamics generate complex high-frequency variability in water quality and non-linear reposes to nutrient loading and environmental forcing in shallow water systems.

Biogeochemical states, rates, and exchanges exhibit linear responses to large nutrient load reductions in a shallow, eutrophic urban estuary - Jeremy M. Testa; Walter R. Boynton; Casey L. S. Hodgkins; Amanda L. Moore; Eva M. Bailey; Johanna Rambo (Limnology and Oceanography, 2022)
We examined responses of water‐column conditions, sediment‐water fluxes, ecosystem metabolism, and nutrient export in the Back River estuary during the past three decades following multiple phases of nutrient load reductions from a large wastewater treatment plant. Total nitrogen (TN) loads from the treatment plant declined from 7000 kg N d −1 in the mid‐1980s to 1500 kg N d −1 following the implementation of enhanced nutrient removal in late 2017. Total phosphorus (TP) loads declined by ~90% from peaks in the mid‐1980s–1990s and have been stable ever since. In response, TN and TP concentrations measured since 1985 show declines that generally mirror that of loads from the treatment plant, and box model computations suggest significant reductions in nutrient export to adjacent Chesapeake Bay. As a consequence, water‐column chlorophyll a (Chl a ) concentrations have declined modestly over the record, despite inter‐annual variability. This reduction in Chl a coincided with a reduced frequency of nitrogen and phosphorus concentrations that would saturate phytoplankton growth, as well as reductions in ecosystem gross primary production and respiration derived from high‐frequency oxygen time‐series. Sediment‐water fluxes of dissolved nitrogen, phosphorus, and oxygen, as well as associated sediment concentrations of nitrogen, phosphorus, and carbon also declined over the record. These temporal patterns were reproduced in a 35‐yr model simulation that suggests a relatively rapid response to reduced organic matter deposition changes. Finally, the recycling of ammonium for a given TN load declined substantially, consistent with high observed rates of denitrification, indicating that well‐mixed estuaries can recover relatively rapidly in response to nutrient remediation.

Supply‐controlled calcium carbonate dissolution decouples the seasonal dissolved oxygen and pH minima in Chesapeake Bay - Jianzhong Su; Wei‐Jun Cai; Jeremy M. Testa; Jean R. Brodeur; Baoshan Chen; K. Michael Scaboo; Ming Li; Chunqi Shen; Margaret Dolan; Yuan‐Yuan Xu; Yafeng Zhang; Najid Hussain (Limnology and Oceanography, 2021)
Acidification can present a stress on organisms and habitats in estuaries in addition to hypoxia. Although oxygen and pH decreases are generally coupled due to aerobic respiration, pH dynamics may be more complex given the multiple modes of buffering in the carbonate system. We studied the seasonal cycle of dissolved oxygen (DO), pH, dissolved inorganic carbon, total alkalinity, and calcium ion (Ca 2+ ) along the main channel of Chesapeake Bay from May to October in 2016. Contrary to the expected co‐occurrence of seasonal DO and pH declines in subsurface water, we found that the pH decline ended in June while the DO decline continued until August in mid‐Chesapeake Bay. We discovered that aerobic respiration was strong from May to August, but carbonate dissolution was minor in May and June and became substantial in August, which buffered further pH declines and caused the seasonal DO and pH minima mismatch. The rate of calcium carbonate (CaCO 3 ) dissolution was not primarily controlled by the saturation state in bottom water, but was instead likely controlled by the supply of CaCO 3 particles. The seasonal variability of Ca 2+ addition in the mid‐bay was connected to Ca 2+ removal in the upper bay, and the timing of high carbonate dissolution coincided with peak seasonal biomass of upper Bay submerged aquatic vegetation. This study suggests a mechanism for a novel decoupling of DO and pH in estuarine waters associated with CaCO 3 , but future studies are needed to fully investigate the seasonality of physical transport and cycling of CaCO 3 .

Seasonal and spatial variability in surface p CO 2 and air–water CO 2 flux in the Chesapeake Bay - Baoshan Chen; Wei‐Jun Cai; Jean R. Brodeur; Najid Hussain; Jeremy M. Testa; Wenfei Ni; Qian Li (Limnology and Oceanography, 2020)
Interactions between riverine inputs, internal cycling, and oceanic exchange result in dynamic variations in the partial pressure of carbon dioxide ( p CO 2 ) in large estuaries. Here, we report the first bay‐wide, annual‐scale observations of surface p CO 2 and air–water CO 2 flux along the main stem of the Chesapeake Bay, revealing large annual variations in p CO 2 (43–3408 μ atm) and a spatial‐dependence of p CO 2 on internal and external drivers. The low salinity upper bay was a net source of CO 2 to the atmosphere (31.2 mmol m −2 d −1 ) supported by inputs of CO 2 ‐rich Susquehanna River water and the respiration of allochthonous organic matter, but part of this region was also characterized by low p CO 2 during spring and fall phytoplankton blooms. p CO 2 decreased downstream due to CO 2 ventilation supported by long water residence times, stratification, mixing with low p CO 2 water masses, and carbon removal by biological uptake. The mesohaline middle bay was a net CO 2 sink (−5.8 mmol m −2 d −1 ) and the polyhaline lower bay was nearly in equilibrium with the atmosphere (1.0 mmol m −2 d −1 ). Although the main stem of the bay was a weak CO 2 source (3.7 ± 3.3 × 10 9 mol C) during the dry hydrologic (calendar) year 2016, our observations showed higher river discharge could decrease CO 2 efflux. In contrast to many other estuaries worldwide that are strong sources of CO 2 to the atmosphere, the Chesapeake Bay and potentially other large estuaries are very weak CO 2 sources in dry years, and could even turn into a CO 2 sink in wet years.

Effects of Wind-Driven Lateral Upwelling on Estuarine Carbonate Chemistry - Ming Li; Renjian Li; Wei-Jun Cai; Jeremy M. Testa; Chunqi Shen (Frontiers in Marine Science, 2020)

Simulated Estuary-Wide Response of Seagrass (Zostera marina) to Future Scenarios of Temperature and Sea Level - Cara R. Scalpone; Jessie C. Jarvis; James M. Vasslides; Jeremy M. Testa; Neil K. Ganju (Frontiers in Marine Science, 2020)

Source partitioning of oxygen‐consuming organic matter in the hypoxic zone of the Chesapeake Bay - Jianzhong Su; Wei‐Jun Cai; Jean Brodeur; Najid Hussain; Baoshan Chen; Jeremy M. Testa; K. Michael Scaboo; Deb P. Jaisi; Qiang Li; Minhan Dai; Jeffrey Cornwell (Limnology and Oceanography, 2020)
We surveyed the carbonate system along the main channel of the Chesapeake Bay in June 2016 to elucidate carbonate dynamics and the associated sources of oxygen‐consuming organic matter. Using a two endmember mixing calculation, chemical proxies, and stoichiometry, we demonstrated that in early summer, dissolved inorganic carbon (DIC) dynamics were controlled by aerobic respiration in the water column (43%), sulfate reduction in the sediment (39%), atmospheric CO 2 invasion (13%), and CaCO 3 dissolution (5%). A mass balance of the DIC concentration and its stable isotope suggested that the apparent δ 13 C of oxygen‐consuming organic matter was −19.4 ± 0.3‰. The bulk composition of particulate organic matter also reflected a dominance of algal material (C/N = ~ 6, δ 13 C > −25‰). Therefore, we concluded that the decomposition of autochthonous organic matter (i.e., eutrophication‐stimulated primary production) was the dominant process consuming oxygen, while allochthonous organic matter (terrestrially derived) made minor contributions to oxygen consumption in the hypoxic zone in June 2016. These findings in the Chesapeake Bay contrast with another hypoxic estuarine ecosystem, the Pearl River Estuary in China where allochthonous organic matter contributed significantly to oxygen consumption. The differences between these two systems in terms of hydrology, quantity and quality of organic matter, and physical characteristics are discussed to yield new insights on the formation and maintenance of hypoxia. In both systems, autochthonous organic matter dominates oxygen depletion, indicating that nutrient management and reduction are useful actions to control and mitigate the occurrence of hypoxia for the restoration of ecosystem.

Fermentation and Anaerobic Oxidation of Organic Carbon in the Oxygen Minimum Zone of the Upwelling Ecosystem Off Concepción, in Central Chile - Benjamín M. Srain; Marcus Sobarzo; Giovanni Daneri; Humberto E. González; Giovanni Testa; Laura Farías; Alex Schwarz; Norma Pérez; Silvio Pantoja-Gutiérrez (Frontiers in Marine Science, 2020)

Spatiotemporal variability of light attenuation and net ecosystem metabolism in a back-barrier estuary - Neil K. Ganju; Jeremy M. Testa; Steven E. Suttles; Alfredo L. Aretxabaleta (Ocean Science, 2020)
Quantifying system-wide biogeochemical dynamics and ecosystem metabolism in estuaries is often attempted using a long-term continuous record at a single site or short-term records at multiple sites due to sampling limitations that preclude long-term monitoring. However, differences in the dominant primary producer at a given location (e.g., phytoplankton versus benthic producers) control diel variations in dissolved oxygen and associated ecosystem metabolism, and they may confound metabolic estimates that do not account for this variability. We hypothesize that even in shallow, well-mixed estuaries there is strong spatiotemporal variability in ecosystem metabolism due to benthic and water-column properties, as well as ensuing feedbacks to sediment resuspension, light attenuation, and primary production. We tested this hypothesis by measuring hydrodynamic properties, biogeochemical variables (fluorescent dissolved organic matter – fDOM, turbidity, chlorophyll a fluorescence, dissolved oxygen), and photosynthetically active radiation (PAR) over 1 year at 15 min intervals at paired channel (unvegetated) and shoal (vegetated by eelgrass) sites in Chincoteague Bay, Maryland–Virginia, USA, a shallow back-barrier estuary. Light attenuation (KdPAR) at all sites was dominated by turbidity from suspended sediment, with lower contributions from fDOM and chlorophyll a. However, there was significant seasonal variability in the resuspension–shear stress relationship on the vegetated shoals, but not in adjacent unvegetated channels. This indicated that KdPAR on the shoals was mediated by submerged aquatic vegetation (SAV) and possibly microphytobenthos presence in the summer, which reduced resuspension and therefore KdPAR. We also found that gross primary production (Pg) and KdPAR were significantly negatively correlated on the shoals and uncorrelated in the channels, indicating that Pg over the vegetated shoals is controlled by a feedback loop between benthic stabilization by SAV and/or microphytobenthos, sediment resuspension, and light availability. Metabolic estimates indicated substantial differences in net ecosystem metabolism between vegetated and unvegetated sites, with the former tending towards net autotrophy in the summer. Ongoing trends of SAV loss in this and other back-barrier estuaries suggest that these systems may also shift towards net heterotrophy, reducing their effectiveness as long-term carbon sinks. With regards to temporal variability, we found that varying sampling frequency between 15 min and 1 d resulted in comparable mean values of biogeochemical variables, but extreme values were missed by daily sampling. In fact, daily resampling minimized the variability between sites and falsely suggested spatial homogeneity in biogeochemistry, emphasizing the need for high-frequency sampling. This study confirms that properly quantifying ecosystem metabolism and associated biogeochemical variability requires characterization of the diverse estuarine environments, even in well-mixed systems, and demonstrates the deficiencies introduced by infrequent sampling to the interpretation of spatial variability.

Influences of a River Dam on Delivery and Fate of Sediments and Particulate Nutrients to the Adjacent Estuary: Case Study of Conowingo Dam and Chesapeake Bay - Cindy M. Palinkas; Jeremy M. Testa; Jeffrey C. Cornwell; Ming Li; Lawrence P. Sanford (Estuaries and Coasts, 2019)

Patterns and Trends in Secchi Disk Depth over Three Decades in the Chesapeake Bay Estuarine Complex - Jeremy M. Testa; Vyacheslav Lyubchich; Qian Zhang (Estuaries and Coasts, 2019)

Chesapeake Bay Inorganic Carbon: Spatial Distribution and Seasonal Variability - Jean R. Brodeur; Baoshan Chen; Jianzhong Su; Yuan-Yuan Xu; Najid Hussain; K. Michael Scaboo; Yafeng Zhang; Jeremy M. Testa; Wei-Jun Cai (Frontiers in Marine Science, 2019)

Breakdown rates and associated nutrient cycling vary between novel crop-derived and natural riparian detritus in aquatic agroecosystems - Jason M. Taylor; Richard E. Lizotte; Sam Testa (Hydrobiologia, 2019)

Season‐specific trends and linkages of nitrogen and oxygen cycles in Chesapeake Bay - Jeremy M. Testa; W. Michael Kemp; Walter R. Boynton (Limnology and Oceanography, 2018)
A three‐decade time series of solute concentrations was combined with a box‐modeling system to analyze long‐term trends in the concentration, production, and transport of dissolved inorganic nitrogen species along the mainstem axis of Chesapeake Bay. Water‐ and salt‐balance calculations associated with box‐modeling provided regional, seasonal, and interannual estimates of net advective and nonadvective transport and net biogeochemical production rates for oxygen and dissolved nitrogen. The strongest decadal trends were observed for decreasing late‐summer ammonium concentrations in bottom layers from brackish to polyhaline bay regions. Contemporaneous trends of increasing late‐summer bottom‐layer dissolved oxygen (O 2 ) concentration were consistent with the observed NH 4 + patterns, suggesting that increasing dissolved O 2 levels may also reflect declining bottom respiration and drive nitrogen loss via increased rates of coupled nitrification–denitrification. Significant (but weaker) trends of increasing nitrate plus nitrite (NO 2+3 − ) concentration and net production were consistent with the notion that increased nitrification may be stimulated by increasing dissolved O 2 concentrations. Sorting bottom water NH 4 + and NO 2+3 − net production rates into two pools (before and after the year 2000) revealed that general seasonal patterns were similar, but recent NH 4 + net production rates were consistently lower and NO 2+3 − and NO 2 − rates higher in summer and fall compared to earlier years, especially in the middle Bay regions. We conclude that late‐season replenishment of oxygen associated with declining nutrient loads induced a negative feedback process, whereby decreased hypoxia suppressed NH 4 + recycling and created conditions favorable for additional nitrogen loss via coupled nitrification–denitrification.

Nutrient- and Climate-Induced Shifts in the Phenology of Linked Biogeochemical Cycles in a Temperate Estuary - Jeremy M. Testa; Rebecca R. Murphy; Damian C. Brady; William M. Kemp (Frontiers in Marine Science, 2018)

The role of heavy metals and polychlorinated biphenyls (PCBs) in the oncogenesis of head and neck tumors and thyroid diseases: a pilot study - V. Petrosino; G. Motta; G. Tenore; M. Coletta; A. Guariglia; D. Testa (BioMetals, 2018)

Oxygen and Nutrient Exchanges at the Sediment-Water Interface: a Global Synthesis and Critique of Estuarine and Coastal Data - W. R. Boynton; M. A. C. Ceballos; E. M. Bailey; C. L. S. Hodgkins; J. L. Humphrey; J. M. Testa (Estuaries and Coasts, 2018)

The colorimetric determination of selectively cleaved adenosines and guanosines in DNA oligomers using bicinchoninic acid and copper - Elizabeth M. Thomas; Stephen M. Testa (JBIC Journal of Biological Inorganic Chemistry, 2017)

Challenges and Directions for the Advancement of Estuarine Ecosystem Science - Jeremy M. Testa; W. Michael Kemp; Lora A. Harris; Ryan J. Woodland; Walter R. Boynton (Ecosystems, 2017)

Progress and Challenges in Coupled Hydrodynamic-Ecological Estuarine Modeling - Neil K. Ganju; Mark J. Brush; Brenda Rashleigh; Alfredo L. Aretxabaleta; Pilar del Barrio; Jason S. Grear; Lora A. Harris; Samuel J. Lake; Grant McCardell; James O’Donnell; David K. Ralston; Richard P. Signell; et al. (Estuaries and Coasts, 2016)

Examining green public procurement using content analysis: existing difficulties for procurers and useful recommendations - Francesco Testa; Paolo Grappio; Natalia M. Gusmerotti; Fabio Iraldo; Marco Frey (Environment, Development and Sustainability, 2016)

Grain yield enhancement through fungicide application on maize hybrids with different susceptibility to northern corn leaf blight - G. Testa; A. Reyneri; F. Cardinale; M. Blandino (Cereal Research Communications, 2015)

Spatial and Temporal Patterns of Winter–Spring Oxygen Depletion in Chesapeake Bay Bottom Water - Jeremy M. Testa; W. Michael Kemp (Estuaries and Coasts, 2014)

Diazinon and Permethrin Mitigation Across a Grass–Wetland Buffer - M. T. Moore; R. Kröger; M. A. Locke; R. E. Lizotte; S. Testa; C. M. Cooper (Bulletin of Environmental Contamination and Toxicology, 2014)

Life history and population dynamics of southern Alaska resident killer whales ( Orcinus orca ) - Craig O. Matkin; J. Ward Testa; Graeme M. Ellis; Eva L. Saulitis (Marine Mammal Science, 2014)
Resident (fish eating) killer whales (Orcinus orca ) in the North Pacific have been the subject of long‐term studies in several geographical regions. The current study examines population parameters in the southern Alaska resident population from 1984 to 2010 and develops a population model. The southern Alaska resident population ranges from southeastern Alaska through the Kodiak archipelago and contains over 700 individuals. We follow the life histories of 343 identifiable whales in 10 pods from two clans born before and during the study. Population parameters were comparable to those of the British Columbia northern resident population during the 1970s and 1980s, except that age of maturity was approximately one year earlier. The average annual rate of increase was slightly higher in Alaska (3.5%) than for the British Columbia northern residents (2.9%) and probably represents a population at r‐max (maximum rate of growth). Reasons for the high growth rate in Alaska could be a recovery following past anthropogenic mortalities, or more likely, a response to increasing salmon returns in recent decades, resulting in an increase in carrying capacity. The slow maturation and low rate of reproductive response makes these whales slow to recover from natural or anthropogenic catastrophes.

The metabolism of aquatic ecosystems: history, applications, and future challenges - Peter A. Staehr; Jeremy M. Testa; W. Michael Kemp; Jon J. Cole; Kaj Sand-Jensen; Stephen V. Smith (Aquatic Sciences, 2012)

Ranunculus latent virus: a strain of artichoke latent virus or a new macluravirus infecting artichoke? - M. Ciuffo; M. Testa; R. Lenzi; M. Turina (Archives of Virology, 2011)

Understanding biological dynamics: following cells and molecules to track functions and mechanisms - A. Palamidessi; I. Testa; E. Frittoli; S. Barozzi; M. Garrè; D. Mazza; P. P. Di Fiore; A. Diaspro; G. Scita; Mario Faretta (European Biophysics Journal, 2010)

Role of spiramycin/cotrimoxazole association in the mother-to-child transmission of toxoplasmosis infection in pregnancy - P. Valentini; M. L. Annunziata; D. F. Angelone; L. Masini; M. Santis; A. Testa; R. L. Grillo; D. Speziale; O. Ranno (European Journal of Clinical Microbiology & Infectious Diseases, 2009)

Role of spiramycin/cotrimoxazole association in the mother-to-child transmission of toxoplasmosis infection in pregnancy - P. Valentini; M. L. Annunziata; D. F. Angelone; L. Masini; M. De Santis; A. Testa; R. L. Grillo; D. Speziale; O. Ranno (European Journal of Clinical Microbiology & Infectious Diseases, 2009)

Long-Term Changes in Water Quality and Productivity in the Patuxent River Estuary: 1985 to 2003 - Jeremy M. Testa; W. Michael Kemp; Walter R. Boynton; James D. Hagy (Estuaries and Coasts, 2008)

Photoactivation of pa-GFP in 3D: optical tools for spatial confinement - I. Testa; M. Garrè; D. Parazzoli; S. Barozzi; I. Ponzanelli; D. Mazza; M. Faretta; A. Diaspro (European Biophysics Journal, 2008)

Exploring Linkages between Abiotic Oceanographic Processes and a Top-trophic Predator in an Antarctic Ecosystem - Kelly M. Proffitt; Robert A. Garrott; Jay J. Rotella; Donald B. Siniff; J. Ward Testa (Ecosystems, 2007)

Development of an in Vitro Rat Intestine Segmental Perfusion Model to Investigate Permeability and Predict Oral Fraction Absorbed - Marc-Etienne Castella; Marianne Reist; Joachim M. Mayer; Jean-Jacques Turban; Bernard Testa; Claire Boursier-Neyret; Bernard Walther; Jean-Marie Delbos; Pierre-Alain Carrupt (Pharmaceutical Research, 2006)

The Esterase-Like Activity of Serum Albumin May Be Due to Cholinesterase Contamination - Nathalie Chapuis; Corinne Brühlmann; Marianne Reist; Pierre-Alain Carrupt; Joachim M. Mayer; Bernard Testa (Pharmaceutical Research, 2001)

A quick method of determining rock surface area for quantification of the invertebrate community - Charles M. Cooper; Sam Testa (Hydrobiologia, 2001)

Co-inoculation of human and murine carcinoma cells induces reciprocal suppression of metastasis by both cell lines - Sheila M. Nielsen-Preiss; James P. Quigley; Jacqueline E. Testa (Clinical & Experimental Metastasis, 1999)

Movements and diving behavior of weaned Weddell seal ( Leptonychotes weddellii ) pups - J. M. Burns; M. A. Castellini; J. W. Testa (Polar Biology, 1999)

A 169-base pair tandem repeat DNA marker for subtelomeric heterochromatin and chromosomal rearrangements in aphids of the Myzus persicae group - Jennifer M. Spence; Roger L. Blackman; Johann M. Testa; Paul D. Ready (Chromosome Research, 1998)

The diet of Weddell seals in McMurdo Sound, Antarctica as determined from scat collections and stable isotope analysis - J. M. Burns; S. J. Trumble; M. A. Castellini; J. W. Testa (Polar Biology, 1998)

Mapping of the Simpson-Golabi-Behmel overgrowth syndrome gene (GPC3) to Chromosome X in human and rat by fluorescence in situ hybridization - T. Shen; G. Sonoda; J. Hamid; M. Li; J. Filmus; R. N. Buick; J. R. Testa (Mammalian Genome, 1997)

Insulin reduces HBsAg production by PLC/PRF/5 human hepatoma cell line - M. Clementi; I. Testa; P. Bagnarelli; A. Festa; P. Pauri; M. Brugia; L. Calegari; C. de Martinis (Archives of Virology, 1984)